PERAN KELUARGA DALAM PEMBINAAN PERKEMBANGAN KEPRIBADIAN MUSLIM PADA ANAK DI DESA KEMUNING KECAMATAN SAMBIT KABUPATEN PONOROGO JAWA TIMUR - huda, Chisbulloh; Noer, Mohammad Fahrudi; Antikasari, Risa Nur (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Abstract This research discusses the Role of the Family in Fostering the Development of Muslim Personality in Children in Kemuning Village, Sambit District, Ponorogo Regency.The research problems formulated in this study are: 1) What is the position of parents in the family as the first and foremost religious educators for children in Kemuning Village, Sambit District, Ponorogo Regency? 2) What factors influence the development of children's personality in Kemuning Village, Sambit District, Ponorogo Regency? 3)How is the role of the family in fostering the development of Muslim personality in children in Kemuning Village, Sambit District, Ponorogo Regency? This research is a case study using a qualitative approach. In terms of data collection techniques, this study uses observation, interviews, and documentation. Meanwhile, the data analysis technique used is qualitative descriptive analysis. The results of the research on the Role of the Family in Fostering the Development of Muslim Personality in Children in Kemuning Village, Sambit District, Ponorogo Regency show that parents (the family) genuinely strive to nurture the Muslim personality in their children. It also indicates that parents (the family) truly take responsibility for guiding their children to become devout Muslims who practice Islamic teachings and avoid its prohibitions in daily life. Thus, the role of parents (the family) in Kemuning Village, Sambit District, Ponorogo Regency, in addition to being the first and foremost educators, is also as caretakers and mentors for their children in daily life, in order to form an insan kamil—a person with a good Muslim personality who aligns with religious teachings and is expected to contribute to religion, the nation, and the country in the future.